The Influence of Job Satisfaction on Organizational Commitment - Hapipuddin Hapipuddin; Zulkifli Musannip Efendi Siregar; Ade Parlaungan Nasution (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
This research aims to determine the effect of job satisfaction on work commitment. The research method was quantitative research. The sample in this research was 30 teachers. The data was processed using SMART PLS analysis techniques. The research results show that there is an influence between job satisfaction and teacher work commitment. This means that increasing teacher job satisfaction will increase teacher commitment to work. Researchers provide suggestions to further increase teacher work commitment by increasing teacher satisfaction in carrying out their duties. Keywords: Job Satisfaction, Organizational Commitment